Success Factor for Project Management on High Rise Building Project - Rozlin Zainal,; Yahya Mohsen Al-Tawil ,; Narimah Kasim,; Sharifah Meryam Shareh Musa,; Musa Mohammed, (Journal of Technology Management and Business, 2019)
Abstract: Success of each project and efficiency is required to achieve a greater advantage over the firms in construction industry today. Effective project management overcomes these types of challenges. Each big construction project company strives to achieve the most efficient and effective project management processes. The success factors which are important for project management in high rise building project success. However the main issues that can lead the project to fail are lack of communication among the project team. This study identifies the project management practices in high rise building, success factor for project management on high rise building and un-success factor for project management. The methodology of this study used questionnaire method and the targeted are contractors’ firms in Johor Bahru with sample size of 200 respondents. This study used descriptive statistical analysis which is frequency and mean by SPPS software. The dominant practice from the analysis for the first objective is comprehensive understanding of the work and process. While, the dominant success factor from the analysis for the second objective are project manager ability to coordinate and motivate team. Finally, the dominant factor from the analysis for the third objective un-success factor which is financial difficulties faced by the contractor. Further study can be performed regarding this topic in different ways or methods such as other provinces or cities of Malaysia; another type of construction projects, such as highways construction project, dam construction project, using another grade of contractors such as G6, G5 and etc.Keywords: Construction, high-rise building, project management, success